TYPE 3 DIABETES: THE MOLECULAR LINK BETWEEN INSULIN RESISTANCE AND NEURODEGENERATION - Temirova Bakhora Khakim qizi,; Kenjaboyeva Sevinch Uktamboyevna,; Odilova Nigora Foziljon qizi,; Hamdamova Farangiz Baxtiyor qizi,; Karimova Nargiza Erkinovna, (TADQIQOTLAR, 2026)
Abstract Type 3 diabetes (T3D) is a proposed term for Alzheimer’s Disease (AD) that represents  a  form  of  diabetes  that  selectively  involves  the  brain.  This  condition  is characterized by brain-specific insulin resistance and insulin deficiency, which triggers a cascade of neurodegenerative processes. This review explores the pathophysiology, clinical presentation, and emerging therapeutic landscape for T3D.